Variables neuropsicológicas y problemas de aprendizaje - Ordoñez Farías, Sonia Luz (My University, 2020)
Neuropsychology changed the perspective about brain functions and mental processes, producing a great development in neuroscience and psychology. The objective of this research is to describe the effect that neuropsychological variables have on learning problems. The methodology applied is descriptive based on the bibliographic review of scientific articles, specialized books and theses. The results show that there is a relationship between the neuropsychological variables (memory, language, learning, executive functions, attention and motor skills) and the capacity that a person has to receive, process, order, classify and store information obtained from external stimuli that develop learning. The neuropsychological variables refer to the auditory, visual, orientation and psychomotor functions which allow the reception of information through the senses, these variables have an important effect on learning problems, if a variable is not worked properly, the person will have an effect on standard development, these affectations are not individual, since all are part of a whole. In addition, there are neuropsychological linguistic and metalinguistic predictors: phonetic perception, phonological awareness and visuospatial ability, becoming necessary predictors for better clarification.
La neuropsicología cambió la perspectiva que se tenía acerca de las funciones cerebrales y los procesos mentales, produciendo así un gran desarrollo en la neurociencia y la psicología. El objetivo de esta investigación es describir el efecto que tienen las variables neuropsicológicas en los problemas de aprendizaje. La metodología aplicada es descriptiva en base a la revisión bibliográfica de artículos científicos, libros especializados y tesis. Los resultados muestran que existe relación de las variables neuropsicológicas (memoria, lenguaje, aprendizaje, funciones ejecutivas atención y motricidad) y la capacidad que tiene una persona para recibir, procesar, ordenar, clasificar y almacenar información obtenida de estímulos externos que desarrollan el aprendizaje. Las variables neuropsicológicas hacen referencia a las funciones auditiva, visual, de orientación y psicomotricidad las cuales permiten la recepción de la información a través de los sentidos, estas variables tienen un efecto importante sobre los problemas de aprendizaje, si una variable no es trabajada de manera apropiada, la persona tendrá una afectación en el desarrollo estándar, estas afectaciones no son de manera individual, puesto que todas son parte de una totalidad. Además, existen predictores neuropsicológicos lingüísticos y metalingüísticos: percepción fonética, conciencia fonológica y habilidad visoespacial, convirtiéndose en predictores necesarios para una mejor clarificación.
Keywords: NEUROPSICOLOGIA; APRENDIZAJE; COMPRENSION LECTORA; METALINGUISTICA